PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VII6 SMP NEGERI 12 PEKANBARU - Didik Kharis Prayudi; Atma Murni; Nahor Murani Hutapea (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by the low of learning achievements of students of SMP Negeri 12 Pekanbaru. This research is aimed at improving the student learning achievements by using the Discovery Learning model. This classroom action research was conducted in VII.6 class of SMP Negeri 12 Pekanbaru in the first semester of the school year 2019/2020. The subjects of this research were grade VII.6 of SMP Negeri 12 Pekanbaru that consists of 38 students with 16 were male and 22 were female. The study was done in two cycles with each cycle consisting of three meetings and one repetition every day. The instruments of this research were a learning device and a data collection. The learning tools consist of syllabus, Lesson Plan (RPP) and Student Worksheet (LKPD). The observation sheets and test results of learning were used as the instruments collection. Based on data analysis of the teacher and the student activity, it found that there is an improvement in the learning process after the Discovery Learning model was applied. The results of the students' mathematics test demonstrate that the number of students in knowledge competence decreased in frequency at low intervals and very low intervals from the basic score (5 learners) to the UH I score (2 learners) and to the UH II score ( 0 students) and an increase in the frequency of students at high and very high intervals from the base score (13 learners) to the UH score I (21 learners) and to the UH II score (24 learners). In the competence of skills there is a decrease in frequency at low and very low intervals from the base score (20 learners) to the UH I score (18 learners) and to the UH score II (10 learners) and an increase in the frequency of learners at high and high intervals once from the base score (3 learners) to the UH score I (5 learners) and to the UH score II (10 learners). The results of this research indicate that the application of the Discovery Learning model can improve the learning process and improve mathematics learning achievements of students in class VII6 of SMP Negeri 12 PekanbaruKeywords: Classroom Action Research, Discovery Learning Model, Mathematics Learning Outcomes